A fast ruthenium polypyridine cage complex photoreleases glutamate with visible or IR light in one and two photon regimes - Salierno, Marcelo Javier (2010)
We introduce a new caged glutamate, based in a ruthenium bipyridyl core, that undergoes heterolytic cleavage after irradiation with visible light with wavelengths up to 532 nm, yielding free glutamate in less than 50 ns. Glutamate photorelease occurs also efficiently following two-photon (2P) excitation at 800 nm, and has a functional cross section of 0.14 GM.